Noematic Neighborhood as a Textual Phenomenon of the Church Schism Era - Alexandr V. Zagumennov (RUDN Journal of Language Studies, Semiotics and Semantics)
The relevance of the proposed article is proved by the revival of the scientific community’s interest in philological hermeneutics as in a general theory of understanding texts. By itself, this theory acts as a special case of the world’ existence doctrine, given in both personal and interpersonal acts of its comprehension. This description allows us to assert that philological hermeneutics can be a linguistic adaptation of phenomenological philosophy. This is exactly what we find in the concept of Doctor of Philology, Professor, Honored Scientist of the Russian Federation Georgy Isaevich Bogin (1929-2001). Based on its theoretical and methodological coordinates, the key concept of our article is noema, the minimum indivisible and further nonseparable unit of meaning. The purpose of the proposed work is modeling based on the set theory in the adaptation of A.F. Losev’s noematic neighborhood by interpreting the content of a formally defined interval between the keyword (“blagodat”) and the syntactically related vocabulary. The linguistic material for the practical part of the article was the most significant works of Archpriest Avvakum (“The Book of Conversations”, “The Book of Interpretations and Morals”, “The Book of Expositions, or the Eternal Gospel” and 4 editions of “The Life description written by himself”). The main methods of our article are the following: firstly, the elaboration of the conceptual content based on the internal contradictions of the formative and formalized in this content, i.e. we are talking about the dialectical method; secondly, the rejection of further judgments about everything that has gone beyond the boundaries of the phrase in the broad sense of the term and the analysis of units in a reduced state, i.e. the phenomenological method; third, the derivation from a set of isolated facts of the general interdependent integrity of the minimum units of meaning, i.e. the modeling method. The preliminary results of our work are as follows. For the first time, the concept of a noematic neighborhood was introduced and theoretically substantiated basing on the set theory and the concept of G.I. Bogin. We presented an algorithm for modeling this semantic structure, dissolved in the texts of the Russian church schism era, and offered prospects for reconstructing the linguistic personality on hermeneutical and phenomenological grounds.